For Peculiarities of Representation of Women's Roles and Their Changes in Women's Magazines: Case of the Magazine Moteris - Siudikienė, Daiva; Stundžė, Lijana (Information & Media, 2021)
For a long time, the patriarchal tradition of portraying a woman as stereotypical has been established, confining her to traditional roles in the family and society. Media publications often become the main source of constructing attitudes and beliefs in society. The peculiarities of portraying women in the media are an important means of constructing women's self-awareness. The purpose of this article – to introduce the research conducted to investigate the peculiarities of representation of the women‘s roles in the women's magazines and their transformation. For implementation this research it has been chosen the largest monthly magazine for the Lithuanian women „Woman“ and the issues have been chosen published in 1990, 2000, 2010 and 2018 to fulfill the qualitative and quantitative content analysis. The transition from the Soviet system to the capitalist society is characterized by transformation of values, the search for national identity, the establishmen the new models of relations in the society, the establishmen to the lifestyle characteristic to the capitalist society, etc. The images presented in the media draw the attention of individuals and shape the public's perception of what a woman should be and what responsibilities are assigned to her.
Keywords: woman; roles; media; representation of women's roles; change of roles